Short-range scattering of Hartree type fractional NLS II. (July 2017) - Cho, Yonggeun; Ozawa, Tohru
Abstract: We prove the small data scattering for Hartree type fractional Schrödinger equation with inverse square potential. This is the border line problem between Strichartz range and weighted space range in view of the method of approach. To show this we carry out a subtle trilinear estimate via fractional Leibniz rule and Balakrishnan's formula. This paper is a sequel of the previous result (Cho, 2017).